2020
DOI: 10.1097/jsm.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Postinjury Psychological Symptoms Between Collegiate Athletes With Concussions and Orthopedic Injuries

Abstract: Patterns of psychological disturbance differ after concussions and orthopedic injures. Further research is warranted to identify the factors contributing to these differences and to develop effective intervention programs to prevent these symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…38 It is unclear whether baseline depressive symptoms directly contribute to worse SRC symptomatology, since the onset of depressive symptoms has also been reported after concussions. 30,52 Many previous studies have evaluated psychological symptoms that develop after SRCs 21,29,36,51 ; however, there is a paucity of information on the influence of preexisting psychological factors on the risk or severity of SRCs. The purpose of this systematic review was to comprehensively evaluate the existing literature and report on the relationship of psychological factors in the incidence and severity of SRCs.…”
mentioning
confidence: 99%
“…38 It is unclear whether baseline depressive symptoms directly contribute to worse SRC symptomatology, since the onset of depressive symptoms has also been reported after concussions. 30,52 Many previous studies have evaluated psychological symptoms that develop after SRCs 21,29,36,51 ; however, there is a paucity of information on the influence of preexisting psychological factors on the risk or severity of SRCs. The purpose of this systematic review was to comprehensively evaluate the existing literature and report on the relationship of psychological factors in the incidence and severity of SRCs.…”
mentioning
confidence: 99%
“…23 Guo et al, reported peak depressive symptoms at one month post-concussive injury. 22 The Comparative Mental Health Responses Between Post-Musculoskeletal Injury and Post-Concussive Injury Among Collegiate... Furthermore, four articles are in agreement that depressive symptoms post-concussive injury steadily decrease after the peak depressive scores.…”
Section: Qualitative Review Of Studies Depression Measures Effect Of Time On Depression Measures Of Concussed Athletesmentioning
confidence: 88%
“…The quality assessment scores of individual studies are shown in Table 1. Within the six included articles, [21][22][23][24][25][26] five included football and basketball, [21][22][23][24][25] four included volleyball, [21][22][23][24] three included wrestling, 21,22,25 soccer, 21,22,24 and field hockey, 21,22,24 two included softball, 21,22 baseball, 21,22 hockey, 23,24 lacrosse, 23,24 and rugby, 23,24 and one included mountain biking 24 and cheerleading. 26 One study did not report the type of sport injury breakdown.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations